The Stress-Strain State of the Tunnel Lining That Crosses the Fault Zone of Soil Blocks during an Earthquake - Mark R. Miller; Evgeniy Y. Titov; Sergey S. Kharitonov; Yong Fang (Communications, 2022)
The study examines the question of the tunnel behavior under seismic or geophysical load in the zone of changes in the hardness of the surrounding soil mass. In the course of the study, the internal forces and displacements arising in the structure of a tunnel in the zone of intersection of the boundaries of soil layers with different properties, in the case when these layers move relative to each other, were determined by analytical and numerical solutions. The data obtained by the analytical method was compared to numerical models using practical examples.